FORMING CUSTOMER LOYALTY THROUGH FACTORS IN MEDIATION OF CUSTOMER SATISFACTION - Hudaya, Agung (Dinasti International Journal of Digital Business Management, 2021)
The purpose of this study is to determine how price, service quality, customer satisfaction on customer loyalty and how much influence, price, service quality on customer satisfaction which has implications for customer loyalty. The sample used in this study amounted to 100 respondents who were taken by simple random sampling technique. Data analysis in this study used Structural Equation Modeling (SEM) which was carried out with the help of the SEM program from Smart PLS 3.0. Besides, this research also proves that the price variable will affect customer satisfaction, then the price will also affect customer loyalty, as well as service quality affects customer satisfaction and will also affect customer loyalty. and also the mediating variable of customer satisfaction which will affect customer loyalty. Blanja.com in Jakarta.